Development of edible gels and films as potential strategy to revalorize entire male pork. (February 2022) - Linares, Ma Belén; Peñaranda, Irene; Iniesta, Celia Ma; Egea, Macarena; Garrido, Ma Dolores
Abstract: Spiced edible gels and films were produced as part of a future technological strategy to improve the quality of pork from entire male by contributing to a decrease in boar taint and improving the texture of the meat. Each formulation, two types of hydrocolloids and two spice mixtures, were tested for their high masking power (mixtures 1 and 2). The thermoreversible hydrocolloids carrageenans (g-C) and agar-agar (g-A) were used in the production of the gels, and maltodextrin + sodium alginate (f-MA) and gelatin (f-G) for the films. The results showed that the films and gels edible had good physical-chemical and mechanical characteristics, providing sufficient stability to act as a vehicle to incorporate spices and condiments into entire male pork, being mixture 2 provided the highest values. While the use of hydrocolloids in the films improved the texture of the meat. Graphical abstract: Image 1 Highlights: Gels and films reached correct mechanical properties to act as vehicles of spices. Films made with hydrocolloids improved the pork sensory texture. Spice mixture 2 had the greatest sensorial impact on the meat matrix. Spiced edible films and gels were an alternative to alleviate boar-tainted pork.